Analysis of Cov-19 Impact on Financial Performance at PT. Bank Rakyat Indonesia (Persero) Tbk and PT. Bank Central Asia, Tbk for 2016-2020 Using Economic Value Added (EVA) and Market Value Added (MVA) Methods - Tommy Kuncara; Ria Agustina (PT FORMOSA CENDEKIA GLOBAL, 2022)
COVID-19 has a negative impact on economic activity, one of the affects is towards financial performance of banks. Where the net profit of each bank decreased and the bank had to restructure credit to its debtors. The purpose of this study was to determine the impact of CoV-19 on the financial performance of PT. Bank Rakyat Indonesia (Persero), Tbk, and PT. Bank Central Asia, Tbk using Economic Value Added (EVA) and Market Value Added (MVA) methods. In this study, the type of data used was secondary data. The analytical method used is descriptive method of data collected and then compiled and analyzed. The results showed that the EVA value at PT. Bank Rakyat Indonesia (Persero) Tbk, experienced fluctuations, although EVA is not stable, this company still produces an EVA value > 0 or positive value, and for MVA it increased in 2016-2019 but in 2020 it decreased, even so the MVA value> 0 or positive. While at PT. Bank Central Asia, Tbk EVA value has increased every year so that the value of EVA> 0, and for the value of MVA has increased every year with the resulting value of MVA> 0.